Development and first use of a novel cylindrical ball bearing phantom for 9-DOF geometric calibrations of flat panel imaging devices used in image-guided ion beam therapy. (25th October 2016) - Zechner, A; Stock, M; Kellner, D; Ziegler, I; Keuschnigg, P; Huber, P; Mayer, U; Sedlmayer, F; Deutschmann, H; Steininger, P
Abstract: Image guidance during highly conformal radiotherapy requires accurate geometric calibration of the moving components of the imager. Due to limited manufacturing accuracy and gravity-induced flex, an x-ray imager's deviation from the nominal geometrical definition has to be corrected for. For this purpose a ball bearing phantom applicable for nine degrees of freedom (9-DOF) calibration of a novel cone-beam computed tomography (CBCT) scanner was designed and validated. In order to ensure accurate automated marker detection, as many uniformly distributed markers as possible should be used with a minimum projected inter-marker distance of 10 mm. Three different marker distributions on the phantom cylinder surface were simulated. First, a fixed number of markers are selected and their coordinates are randomly generated. Second, the quasi-random method is represented by setting a constraint on the marker distances in the projections. The third approach generates the ball coordinates helically based on the Golden ratio, ϕ . Projection images of the phantom incorporating the CBCT scanner's geometry were simulated and analysed with respect to uniform distribution and intra-marker distance. Based on the evaluations a phantom prototype was manufactured and validated by a series of flexmap calibration measurements and analyses. The simulation with randomly distributed markers as well as the quasi-random approach showed an insufficient uniformity of the distribution over the detector area. The best compromise between uniform distribution and a high packing fraction of balls is provided by the Golden section approach. A prototype was manufactured accordingly. The phantom was validated for 9-DOF geometric calibrations of the CBCT scanner with independently moveable source and detector arms. A novel flexmap calibration phantom intended for 9-DOF was developed. The ball bearing distribution based on the Golden section was found to be highly advantageous. The phantom showed satisfying results for calibrations of the CBCT scanner and provides the basis for further flexmap correction and reconstruction developments.